2012
DOI: 10.1002/jmri.23645
|View full text |Cite
|
Sign up to set email alerts
|

Brain perfusion imaging: How does it work and what should I use?

Abstract: In the last 15 years there has been a relative explosion in the number of magnetic resonance imaging (MRI) techniques and developments related to cerebral perfusion. Given the variety of perfusion methods available, it is often difficult to decide which technique would be best for a particular clinical question or patient. In this review article we discuss the more common techniques, review how they are performed, and summarize the optimal technique or techniques for a variety of clinical situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 78 publications
0
35
0
1
Order By: Relevance
“…[189][190][191][192] Perfusion studies using either arterial spin labeling (ASL) 193 or dynamic susceptibility contrast-enhanced perfusionweighted imaging (DSC PWI) 194 have demonstrated reduced CBF in moderate to severe TBI and in chronic mTBI patients. Furthermore, experimental animal models in moderate to severe TBI have demonstrated a decrease in venous blood oxygenation that accompanies the decrease in arterial blood supply, 195 which is suggestive of brain tissue at risk for hypoxia.…”
Section: Perfusion Imagingmentioning
confidence: 99%
See 3 more Smart Citations
“…[189][190][191][192] Perfusion studies using either arterial spin labeling (ASL) 193 or dynamic susceptibility contrast-enhanced perfusionweighted imaging (DSC PWI) 194 have demonstrated reduced CBF in moderate to severe TBI and in chronic mTBI patients. Furthermore, experimental animal models in moderate to severe TBI have demonstrated a decrease in venous blood oxygenation that accompanies the decrease in arterial blood supply, 195 which is suggestive of brain tissue at risk for hypoxia.…”
Section: Perfusion Imagingmentioning
confidence: 99%
“…ASL can quantify absolute CBF, 192,206,207 and a few studies reported perfusion deficits in chronic TBI patients using ASL. Most recently, the MR perfusion study community unanimously recommended the use of pseudocontinuous ASL (pCASL) with 3D gradient and spin echo (GRASE) as the readout for absolute CBF quantification.…”
Section: Perfusion Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative data processing includes data cleaning (removal of individual images with noise spikes or severe motion artifact), realignment (separately for label and control images), spatial smoothing, and calculation of mean cerebral blood flow (CBF) maps; our methods and experience with this technique has been well documented (Deibler, et al, 2008a,Deibler, et al, 2008b,Deibler, et al, 2008c,Johnston, et al, 2013,Maldjian, et al, 2009,Maldjian, et al, 2008,McGehee, et al, 2012,Pollock, et al, 2008a,Pollock, et al, 2008b,Pollock, et al, 2009a,Pollock, et al, 2009b,Pollock, et al, 2008c,Pollock, et al, 2011,Pollock, et al, 2009c,Tan, et al, 2009,Watts, et al, 2013). The CBF maps were normalized to MNI space by coregistering to the T1 structural data using SPM8, and then combining this transformation matrix with the parameters computed in the VBM8 normalization procedure, allowing derivation of the gray matter cerebral blood flow (GMCBF) measure analyzed.…”
Section: Methodsmentioning
confidence: 99%